2007
DOI: 10.1021/ja071471p
|View full text |Cite
|
Sign up to set email alerts
|

Antibiofouling Polymer-Coated Gold Nanoparticles as a Contrast Agent for in Vivo X-ray Computed Tomography Imaging

Abstract: Current computed tomography (CT) contrast agents such as iodine-based compounds have several limitations, including short imaging times due to rapid renal clearance, renal toxicity, and vascular permeation. Here, we describe a new CT contrast agent based on gold nanoparticles (GNPs) that overcomes these limitations. Because gold has a higher atomic number and X-ray absorption coefficient than iodine, we expected that GNPs can be used as CT contrast agents. We prepared uniform GNPs ( approximately 30 nm in diam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

16
501
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 827 publications
(519 citation statements)
references
References 53 publications
16
501
2
Order By: Relevance
“…Additionally, QDs have been shown to remain in major organs for months after injection producing immunogenic reactions in vivo [352][353][354][355]. Iodinated agents are also less than ideal because of their biological toxicity and short circulation time in vivo [356][357][358]. For example, Kim et al reported that when Ultravist, an iodine based contrast agent, was used in a rat model the circulation time was less than 10 min compared to that of 30 nm spherical Au nanoparticles which circulated in vivo for over 4 h [356].…”
Section: Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, QDs have been shown to remain in major organs for months after injection producing immunogenic reactions in vivo [352][353][354][355]. Iodinated agents are also less than ideal because of their biological toxicity and short circulation time in vivo [356][357][358]. For example, Kim et al reported that when Ultravist, an iodine based contrast agent, was used in a rat model the circulation time was less than 10 min compared to that of 30 nm spherical Au nanoparticles which circulated in vivo for over 4 h [356].…”
Section: Imagingmentioning
confidence: 99%
“…In addition to their biocompatibility, Au nanoparticles have longer in vivo circulation times during the imaging process and in some cases faster elimination time post-procedure [356,[363][364][365]. Additionally, since the atomic number of Au is higher than that of iodine, Au nanostructures have higher absorption efficiencies which means that in vivo contrast will be enhanced [35,356,364,366].…”
Section: Imagingmentioning
confidence: 99%
“…Among these nanoparticles, gold nanoparticles have been extensively exploited for various applications including drug delivery, 1-4 imaging agents, [5][6][7][8] biosensors, [9][10][11][12] and computed tomography (CT) contrast agents [13][14][15][16][17] because they have many advantages such as low cytotoxicity, easy size control, high x-ray absorption, unique optical and electrical properties. Stability of gold nanoparticles under physiological conditions is key step for biomedical application.…”
mentioning
confidence: 99%
“…Another key is the immobilization or conjugation of bioactive molecules on gold nanoparticles for targeted drug delivery, molecular imaging, and in vitro diagnosis. To satisfy these key requirements, we developed a novel random copolymer composed of a "surface anchor part" (thiol group), 13,14,[18][19][20] "antibiofouling part" (PEG), 13,15,[21][22][23][24][25] and "bioreactivity part" (carboxyl group) for gold surface modification in particular.…”
mentioning
confidence: 99%
“…5 In our previous study, we demonstrated the PEG coated gold nanoparticles can be used as a novel CT contrast agent for blood pool imaging (angiography) and for diagnosis of hepatoma, suggesting gold nanoparticle-based CT contrast agent may be able to overcome limitations of conventional iodine based contrast agents. 6 On the other hand, magnetic resonance imaging (MRI) has advantages over CT such as high spatial resolution and sensitivity. Superparamagnetic iron oxide nanoparticles (SPIONs) have been shown to be useful as MRI contrast agents and drug delivery vehicles.…”
mentioning
confidence: 99%